2014
DOI: 10.5897/jmpr2013.5549
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant age on the content and composition of essential oil of Cymbopogon citratus (DC.) Stapf.

Abstract: An experiment was carried out in Viçosa, Brazil to evaluate the influence of plant age (3, 6, 9 and 12 months) on the content and chemical composition of essential oils from lemon grass, using a completely randomized design with three replications. The plants were harvested between 7:00 and 8:30 a.m, and harvesting cut made at 20 cm height from the base of the leaf. The collected material was immediately taken to the laboratory where the leaves were selected, and subsequent determination of moisture content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…When studying the effect of the Artemisia annua harvest age on essential oil production, Damtew et al [48] demonstrated that there was no change in the essential oil content, but the content of artemisinin, an antimalarial compound, was significantly altered. The same result was found by Rocha et al [49] when studying the influence of the age of Cymbopogon citratus (lemon grass) on the chemical composition of the essential oil of this species. The authors reported that there was no change in the extracted oil content, only in the chemical composition.…”
Section: Compoundsupporting
confidence: 83%
“…When studying the effect of the Artemisia annua harvest age on essential oil production, Damtew et al [48] demonstrated that there was no change in the essential oil content, but the content of artemisinin, an antimalarial compound, was significantly altered. The same result was found by Rocha et al [49] when studying the influence of the age of Cymbopogon citratus (lemon grass) on the chemical composition of the essential oil of this species. The authors reported that there was no change in the extracted oil content, only in the chemical composition.…”
Section: Compoundsupporting
confidence: 83%
“…3). Research on lemon balm [Nurzyńska-Wierdak et al 2014] and lemon grass [Rocha et al 2014] shows that plant age may cause differences in the content of essential oil to a lesser extent than in its chemical composition. Santos et al [2012], on the other hand, demonstrated that in the case of harvest of Alpinia zerumbet (Zingiberaceae) leaves, with increasing age there is a significant increase in plant biomass as well as in essential oil content and yield.…”
Section: Resultsmentioning
confidence: 99%
“…The findings from some other studies were slightly different: 80.0% [ 48 ], 81.04% [ 40 ], and 83.46% [ 41 ]. The difference in the EO yield and the chemical composition of lemongrass and star anise EOs were affected by many factors, such as plant genotype, plant age, maturity stage, harvesting stage, primary developmental period, quality of raw plant materials, and good management practice of cultivation [ 49 , 50 , 51 ]. The cropping time, stage of the plant, geographic distribution, environmental factors, and extraction and distillation methods all affected the quality and quantity of plant EOs [ 48 , 52 ].…”
Section: Discussionmentioning
confidence: 99%